2014
DOI: 10.4028/www.scientific.net/amr.1040.13
|View full text |Cite
|
Sign up to set email alerts
|

Design and Investigation of Hard Metal Composites Modified by Nanoparticles

Abstract: The influence of nanoparticles additives on the hard metals properties has been investigated. Nanoparticles introduced into a binder of average size decrease the metal interlayer and therefore increase the strength of binder and composite as a whole. The reduction of the carbide grain average size was found as well (owing to nanoparticles blocking influence on re-crystallization). Besides, the internal thermotension and adhesion wear decrease at high speed cutting (especially for stainless steel) in comparisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Аl2O3, with the specific surface being 12 m 2 /g. Previous experimental researches and the data of other authors [3,4] reliably it is established that there is a direct functional relationship between structural parameters (the average size of carbide grain, the average thickness of the interlayer binder, contactness of carbide grains, volume fraction of solid phase and binder, ets.) and strength characteristics of composites.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Аl2O3, with the specific surface being 12 m 2 /g. Previous experimental researches and the data of other authors [3,4] reliably it is established that there is a direct functional relationship between structural parameters (the average size of carbide grain, the average thickness of the interlayer binder, contactness of carbide grains, volume fraction of solid phase and binder, ets.) and strength characteristics of composites.…”
Section: Resultsmentioning
confidence: 91%
“…where: β0structure coefficient depend of the of carbide morphology; h -the binder layer between nanoparticles -df, νhvolume of binder. Solving this equations system of (1, 2) and using the results of modeling developed previously [3,4,6] for WC-Co-nanoAl2O3 (ZrO2) and data presented in [7] can be determine the volume of additives in the structure and optimal ratios sizes dm / df and volumes νm / νf. Obtained As a result allow the possibility to obtain compacts highest density of compound.…”
Section: Resultsmentioning
confidence: 99%
“…The hardness and density parameters of the material do not differ significantly from the base material and are at the level: but the values of the microhardness of the interlayer of binder material -cobalt, which was estimated with the help of nanoindentation, are slightly increased, since the known effect of dispersive hardening at the level of structural fragments (Co-Al 2 O 3 ) is realized. On the basis of the experimentally obtained positive results and the revealed features of the structure formation of heterophase carbide composites, the geometric model described in detail [4,8] was refined and corrected, including the known and new density positions packaging of bimodal and polymodal dispersed systems. A new model of heterogeneous carbide structures assumes the use of composite submicron powders (WC-Co), obtained by various methods, which provides the maximum packing density and high homogeneity of the mutual distribution of phase constituents of the composite (Fig.…”
Section: Type 3 Polydesperse Heterogeneous Structurementioning
confidence: 99%
“…There are known effective methods and processing technologies enabling the retention of submicron carbide grains due to introduction of nanosized powders of vanadium, chromium, tantalum carbides or other nanopowders of oxides, nitrides which act as growth inhibitors of the main phase WC in sintering process [3]. In [4] it is shown that the efficiency of modification of the hard metals by nanoparticles of inhibitors Al 2 O 3 substantially depends on the size, concentration and volume fraction of all components of WC-Co-Al 2 O 3 composite. Excessive concentration of nanoparticles in the local volume between carbide grains increases the degree of contact and the formation of agglomerates.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical values of composite particle parameters and thickness of a coating layer from metal binder on carbide composite powders can be also determined basing on a simple ratio: Vh/Vcm = 6h/dm, where: Vcm -volume of composite particle. Solving this system of equations and using equations of the geometric model developed earlier [10,12] for WC-Co-nanoAl 2 O 3 (ZrO 2 ) the optimum volume of modifying additives at different ratios of average sizes d m / d f and volume of particles ν m / ν f can be determined In accordance with the geometric model calculation a prediction about the amount of additives needed to obtain compacts with the highest packing density is possible. Estimates were made in the carbide phase size in the range of d m (WC) from 0.5 to 3 µm and for ultrafine particle sizes of 0,008 to 0.1 µm.…”
Section: Theory/calculationmentioning
confidence: 99%